Elastic-plastic analysis of antiplane crack near crack surface region - 易志坚 谷建义 何小兵 马银华 杨庆国 彭凯 黄锋 黄宗明 (Applied mathematics and mechanics, 2010)
The elastic-plastic stress distribution and the elastic-plastic boundary con- figuration near a crack surface region are significant but hard to obtain by means of the conventional analysis. A crack line analysis method is developed in this paper by consid- ering the crack surface as an extension of the crack line. The stresses in the plastic zone, the length, and the unit normal vector of the elastic-plastic boundary near a crack surface region are obtained for an antiplane crack in an elastic-perfectly plastic solid. The usual small scale yielding assumptions are not needed in the analysis.